Financial Sustainability of Microfinance Institutions : Evidence from India - Singh, Amit Kumar; Goel, Sandeep Kumar; Negi, Devyani (Indian Journal of Research in Capital Markets, 2023)
Purpose : The study aimed to analyze the financial sustainability of microfinance institutions (MFIs) and identify the factors that affected the financial sustainability measures in the presence of the social goal of achieving maximum outreach. Methodology : The study was based on 30 MFIs that were active in India between 2010 and 2019. Financial sustainability was the dependent variable in the study, and it was assessed using three proxies: PRM, operating self-sufficiency, and return on asset. The independent variables were the total loan portfolio, operational expense ratio, loan loss rate (LLR), debt-to-equity ratio, cost per borrower (CPB), and average loan balance per borrower to GNI per capita. The EViews student version was used to analyze panel data using t-test, ANOVA, correlation, and regression. Findings : The study’s outcome reflected that almost all the explanatory variables significantly affected financial sustainability during the study period. Two factors, i.e., debt-equity and operating expense ratios, displayed outcomes contrary to expectations. It was also discovered that MFIs must strike a balance between depth of outreach and financial sustainability. Practical Implications : According to the report, profit nature and non-banking financial institutions, MFIs must improve their financial viability. Furthermore, these institutions must keep their CPB as low as feasible, extend their operations, i.e., lending levels, and keep their LLR as low as possible by personalizing their goods. They also wanted to guarantee that their outreach was both deep and broad. Originality : This study was pertinent because there haven’t been many studies on MFIs in India recently. Additionally, this study considered CPB and average loan balance per borrower, two less-studied variables.